Językowe kreacje litewskich magnatów w Potopie Henryka Sienkiewicza - Pietrzak, Magdalena (Acta Universitatis Lodziensis. Folia Linguistica, 2007)
The article discusses the fragment of the reality evoked in Potop, and its main issue concerns the images of Lithuanian magnates in the 17th century. In the article aristocratic mentality has been analyzed and reconstructed in detail. The author also points out linguistic ways of creating this social class.